2022
DOI: 10.12791/ksbec.2022.31.1.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Greenhouse Strawberry Production Using Machine Learning Algorithm

Abstract: Strawberry is a stand-out cultivating fruit in Korea. The optimum production of strawberry is highly dependent on growing environment. Smart farm technology, and automatic monitoring and control system maintain a favorable environment for strawberry growth in greenhouses, as well as play an important role to improve production. Moreover, physiological parameters of strawberry plant and it is surrounding environment may allow to give an idea on production of strawberry. Therefore, this study intends to build a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…In addition, the physiological parameters of strawberry plants also determine the amount of strawberry production. Modeling of plant physiological parameters and environmental conditioning of plants using machine learning can be used to predict the increase in strawberry production (Kim, 2022). Observations on the growth of strawberry plants in each plot at week 6 showed that flower buds had appeared and were ready to start bearing fruit.…”
Section: Strawberry Observation Results Smart Greenhouse and Ordinary...mentioning
confidence: 99%
“…In addition, the physiological parameters of strawberry plants also determine the amount of strawberry production. Modeling of plant physiological parameters and environmental conditioning of plants using machine learning can be used to predict the increase in strawberry production (Kim, 2022). Observations on the growth of strawberry plants in each plot at week 6 showed that flower buds had appeared and were ready to start bearing fruit.…”
Section: Strawberry Observation Results Smart Greenhouse and Ordinary...mentioning
confidence: 99%